Weeds find a way - Jenson-Elliott, Cynthia L. (Beach Lane Books, 2014)
Describes some of the ways that weeds live and grow in the most hostile environments, such as a tangle of tree roots or a crack in the cellar of an old house, where other plants cannot thrive.